2009
DOI: 10.1128/aac.00647-09
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein Processing Is Essential for Resistance of Mycobacterium tuberculosis to Malachite Green

Abstract: Malachite green, a synthetic antimicrobial dye, has been used for over 50 years in mycobacterial culture medium to inhibit the growth of contaminants. The molecular basis of mycobacterial resistance to malachite green is unknown, although the presence of malachite green-reducing enzymes in the cell envelope has been suggested. The objective of this study was to investigate the role of lipoproteins in resistance of Mycobacterium tuberculosis to malachite green. The replication of an M. tuberculosis lipoprotein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 20 publications
2
33
0
2
Order By: Relevance
“…Second, increased permeability of cells exposed to cell wall targeting antibiotics could facilitate the access of malachite green to its molecular target(s). Consistent with this interpretation, two recent reports demonstrated that mutant strains of mycobacteria with increased cell wall permeability are hypersensitive to malachite green (3,4). Third, antibiotic-mediated killing has been linked to the production of reactive oxygen species (ROS) in Gram-negative and Gram-positive bacteria (7), and malachite green has been shown to trigger ROS production via an unknown mechanism (18).…”
Section: Discussionsupporting
confidence: 50%
“…Second, increased permeability of cells exposed to cell wall targeting antibiotics could facilitate the access of malachite green to its molecular target(s). Consistent with this interpretation, two recent reports demonstrated that mutant strains of mycobacteria with increased cell wall permeability are hypersensitive to malachite green (3,4). Third, antibiotic-mediated killing has been linked to the production of reactive oxygen species (ROS) in Gram-negative and Gram-positive bacteria (7), and malachite green has been shown to trigger ROS production via an unknown mechanism (18).…”
Section: Discussionsupporting
confidence: 50%
“…3B). Similar diminished ability of Mtb mutants to form colonies on solid medium has been previously attributed to disruption of cell wall integrity, resulting in an increased susceptibility to chaotropic or bacteriostatic agents (such as Malachite green, ordinarily incorporated in solid media for mycobacterial culture) (26). However, the persistence of the deficiency to form colony on Malachite green-free agar medium (Fig.…”
Section: Initiation and Elongation Of The Fasc Mannosyl Appendages Rementioning
confidence: 81%
“…The lspA mutant showed increased sensitivity to first-line antituberculosis drugs and was essential for resistance to malachite green (Banaei et al, 2009). Existing information for this gene is limited and no information is available regarding its regulation.…”
Section: Introductionmentioning
confidence: 98%